A comparative study on constraint parameters for characterizing fracture toughness of X60 and X100 pipe steels. (November 2022) - Qian, Cheng; Liang, Jie; Huang, Yifan; Kang, Jidong; Gianetto, James
Highlights: R -curves are higher for tension vs bending, shallow- vs deep-cracked fracture tests. Eleven constraint parameters are evaluated using FEA for X60 and X100 pipe steels. All constraint parameters can correlate fracture toughness to constraint level. Ap correlates the best with fracture toughness among eleven constraint parameters. Normalized Ap can correlate all tested specimens by a linear master curve. Abstract: The fracture toughness resistance curve (e.g., J - R curve and crack tip opening displacement ( CTOD ) or δ - R curve) is important in facilitating strain-based design and integrity assessment of oil and gas pipelines, where influence of ground movement and presence of planar weld flaws must be accounted for. In the present study, duplicate single edge notched bend (SE(B)) and clamped single edge notched tension (SE(T)) specimens with two different initial crack lengths were tested at room temperature for longitudinally-oriented specimens machined from X60 and X100 pipe steels where the notch is along the through-thickness direction. The results showed the expected trends of higher fracture toughness resistance curves for shallow-cracked over deep-cracked specimen types and tension over bending loading modes. Eleven constraint parameters (i.e., QHRR, QSSY, QLM, QBM, A 2, A 2 BM, h, Tz, Cp, Ap, Vp ) were calculated based on 3-D finite element analysis for all tested SE(B) and SE(T) specimens. The results indicated that the shallow-cracked SE(B) specimens exhibit a constraint condition similar to the intrinsically low-constraint deep-cracked SE(T) specimens made of the X60 pipe steel. Among all of the constraint parameters, the Ap parameter based on the equivalent plastic strain isoline was found to correlate the best to the material fracture toughness for currently tested specimens. Furthermore, a linear master curve between various critical fracture toughness values and Ap parameter was obtained for all the tested specimens with different crack lengths, loading modes and pipe steels.